Ausgebürgert unter dem Hakenkreuz. Rassisch und politisch verfolgte Rechtsanwälte : Biographische Dokumentation einer Spurensuche zur deutschen Emigration nach 1933 - Schumacher, Matin (Aschendorff Verlag, 2023)
Biographical documentation of a search for traces of German emigration after 1933 During the National Socialist era, thousands of emigrants were deprived of their German citizenship. This is the first time that this state injustice has been documented for a group of people. Sources and research on the history of the legal profession in the "Third Reich", the genesis of the expatriation law of 14 July 1933 and the practice of bureaucratic persecution are dealt with in an introductory section. In addition, the consequential punishment of academic expatriation is demonstrated for the universities with law faculties. Affected by the punitive expatriation were hundreds of lawyers, among them half a dozen female lawyers. 610 short biographies recall both luminaries and unknown representatives of the profession. The lawyers who were declared "deprived of German citizenship" were, with few exceptions, Jews, stigmatised and persecuted as Jewish lawyers. Only a few of the lawyers expelled from their profession and homeland returned from exile. Among them were the lawyers Fritz Löwenthal, Rudolf Katz and Friedrich Wilhelm Wagner, who were expatriated after 1933. Appointed to the Parliamentary Council, they voted for the adoption of the Basic Law on 8 May 1949. While Löwenthal retired from politics, Katz served as Minister of Justice in Kiel until 1950. In 1951, he was elected by the Bundesrat as a judge of the newly founded Federal Constitutional Court. Wagner had been a member of the German Bundestag since 1949. In 1961, he moved from Bonn to Karlsruhe, and succeeded Katz as a judge of the Second Senate and Vice-President of the constitutional body